Pristine academic research - Gutiérrez Gómez, Edgar (2019)
The university is a community of teachers and academics with freedom of thought, who surpassed the dissimilar cycles in their historical progress. Its existence is justified by its entelechy staff, such as Mariátegui's sentence: "The University had to give it, therefore, this intellectual militia." (2012, p, 221). Regardless, on the academic ego that makes reigning universities competent, as a product of a thorough escort by the National Superintendence of Higher University Education (SUNEDU), research is decisive to redeem the reason for their existence of these universities in their geographical area where It has been erected.